An intermediate layer structure of all-perovskite tandem battery based on low-dimensional carbon materials

By using low-dimensional carbon materials as charge composite materials in all-perovskite stacked batteries, the problems of high cost and parasitic absorption of traditional precious metal materials are solved, and more efficient photoelectric conversion and stability are achieved.

CN119403348BActive Publication Date: 2025-04-11WUXI YONGJIA LIGHT ENERGY TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411975211.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

In existing all-perovskite stacked batteries, evaporated gold or Sputtering ITO, as a charged composite, has high costs, precious metal diffusion and parasitic absorption, which limits the improvement of battery efficiency.

Method used

The intermediate layer structure based on low-dimensional carbon materials, including electron transport layer, ALD dense protective layer, low-dimensional carbon material charge composite layer and hole transport layer, is prepared through deposition and annealing technology to replace traditional precious metal charge composite materials.

Benefits of technology

It reduces material and equipment costs, reduces parasitic absorption, improves device stability, and effectively improves the photoelectric conversion efficiency of all-perovskite stacked batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119403348B_ABST
    Figure CN119403348B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of solar cells, specifically, an intermediate layer structure of a full perovskite tandem battery based on low-dimensional carbon materials, including a wide bandgap perovskite half-cell at the bottom and a narrow bandgap perovskite half-cell at the top, and an intermediate layer structure is arranged between the wide bandgap perovskite half-cell and the narrow bandgap perovskite half-cell; the intermediate layer structure includes an electron transport layer I, an ALD dense protection layer, a low-dimensional carbon material charge recombination layer and a hole transport layer II arranged from bottom to top; finally, electrodes are evaporated and packaged to prepare a complete full perovskite tandem solar cell. This scheme not only greatly reduces the cost, but also effectively reduces parasitic absorption and shortens the deposition time, while avoiding the diffusion of precious metals and significantly improving the stability of the device. This scheme is of great significance to the industrialization of the full perovskite tandem calcium battery technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solar cells, and in particular to an intermediate layer structure of a full perovskite stacked cell based on low-dimensional carbon materials. Background Art

[0002] Organic-inorganic hybrid lead halide perovskite cells (PSCs) have rapidly become the leader in the new generation of photovoltaic technology due to their high efficiency, huge cost reduction potential, widely adjustable bandgap and extremely wide application scenarios.

[0003] The efficiency record of a single-cell perovskite battery has reached 26.7%, comparable to crystalline silicon batteries. However, due to the limitation of the Schottky-Queisser limit of a single-cell battery (theoretical efficiency upper limit ~33%), the room for efficiency improvement has become smaller and smaller. Therefore, the development of tandem battery technology is the long-term direction for the future development of perovskite photovoltaics. It is worth noting that the cost of perovskite materials in the entire perovskite battery device is less than 5%, and the perovskite band gap can be adjusted over a wide range. Therefore, perovskite materials are naturally suitable for multi-cell tandem battery devices. Full perovskite tandem batteries are one of the technical solutions that can greatly improve the upper limit of battery conversion efficiency (~45%) without significantly increasing costs. Full perovskite tandem batteries are mainly composed of transparent conductive glass, wide bandgap perovskite (WBG) half-cells, intermediate layers, and narrow bandgap perovskite (NBG) half-cells. Compared with single-cell perovskite batteries, in addition to having an additional layer of perovskite, the main core and technical difficulties lie in the material and structural design of the intermediate layer.

[0004] The intermediate layer structure of the all-perovskite battery generally needs to include: an electron transport layer (extracting electrons from a wide bandgap battery, generally N-type materials such as fullerene), a hole transport layer (extracting holes from a narrow bandgap battery, generally P-type materials such as PEDOT:PSS), a dense protective layer (protecting the wide bandgap perovskite layer from damage, generally a tin dioxide layer deposited by atomic layer deposition (ALD)), and a charge composite material (effectively combining the electrons and holes extracted from the two layers of perovskite, generally an evaporated gold or magnetron sputtered ITO layer).

[0005] The quality of the charge composite material directly determines the efficiency loss after the two batteries are connected in series, which is a crucial part. However, both the evaporated gold and Sputter's ITO layer are very expensive in terms of material cost, equipment cost and energy consumption. On the other hand, the intermediate layer based on gold (~2 nm) or ITO (~100 nm) has significant parasitic absorption of visible light, which will directly compete with the perovskite layer for light energy, thereby limiting the upper limit of the efficiency of the stacked battery.

[0006] Therefore, developing a charge composite material that is cheap, chemically stable, easy to prepare, and has no parasitic absorption is an urgent problem to be solved for the successful industrialization of all-perovskite tandem cells and the entire perovskite photovoltaic field. Summary of the invention

[0007] The purpose of the present invention is to overcome the above-mentioned problems of the prior art and provide an intermediate layer structure of a full perovskite tandem battery based on a low-dimensional carbon material, so as to solve the technical problems in the prior art that both the evaporated gold and the Sputter ITO layer are very expensive in terms of material cost, equipment cost and energy consumption, and the aforementioned intermediate layers based on gold (~2 nm) or ITO (~100 nm) have significant parasitic absorption of visible light, which will directly compete with the perovskite layer for light energy, thereby limiting the upper limit of the efficiency of the tandem battery.

[0008] The above objectives are achieved through the following technical solutions:

[0009] An all-perovskite stacked battery intermediate layer structure based on low-dimensional carbon materials, comprising a wide bandgap perovskite half-cell at the bottom and a narrow bandgap perovskite half-cell at the top, wherein an intermediate layer structure is arranged between the wide bandgap perovskite half-cell and the narrow bandgap perovskite half-cell;

[0010] The intermediate layer structure includes an electron transport layer I, an ALD dense protection layer, a low-dimensional carbon material charge recombination layer and a hole transport layer II arranged from bottom to top, and the preparation steps are as follows:

[0011] Step (1) preparing a layer of the electron transport layer I on the top of the wide bandgap perovskite half-cell;

[0012] Step (2) preparing a layer of the ALD dense protective layer on the electron transport layer I by ALD method;

[0013] Step (3) After the ALD dense protective layer is cooled to room temperature, a low-dimensional carbon material precursor solution is disposed on the ALD dense protective layer by deposition to obtain the low-dimensional carbon material charge recombination layer, and annealing and cooling to room temperature; the annealing temperature is 60° C. to 150° C., and the annealing time is 1 minute to 100 minutes;

[0014] Step (4) preparing a hole transport layer II acting on the narrow bandgap perovskite half-cell on the low-dimensional carbon material charge recombination layer, annealing and cooling to room temperature.

[0015] Furthermore, the low-dimensional carbon material precursor solution is a high-polarity solvent with a concentration range of 0.01 to 10 mg / mL.

[0016] Furthermore, in step (3), the low-dimensional carbon material precursor liquid is disposed on the ALD dense protective layer by a deposition method, and the deposition method includes a dynamic spin coating method and a solution method, wherein:

[0017] The rotation speed of the dynamic spin coating method is 3000 to 10000 rpm, and the time is 5 to 100 seconds;

[0018] The solution method is any one of spraying, dipping and slit coating.

[0019] Furthermore, the raw material of the low-dimensional carbon material charge recombination layer is a low-dimensional carbon material, including any combination of one or more of zero-dimensional carbon material, one-dimensional carbon material and two-dimensional carbon material.

[0020] Furthermore, the wide bandgap perovskite half-cell comprises a hole transport layer I, a wide bandgap perovskite layer and a wide bandgap perovskite surface modification layer arranged from bottom to top;

[0021] The narrow-bandgap perovskite half-cell comprises a narrow-bandgap perovskite layer, a narrow-bandgap perovskite surface modification layer and an electron transport layer II arranged from bottom to top.

[0022] Furthermore, the preparation steps of the wide bandgap perovskite half-cell are as follows:

[0023] Disposing a layer of the hole transport layer I on a clean conductive substrate, annealing and cooling to room temperature;

[0024] Preparing a layer of the wide bandgap perovskite layer having the wide bandgap perovskite surface modification layer on the hole transport layer I, annealing and cooling to room temperature;

[0025] The preparation steps of the narrow bandgap perovskite half-cell are as follows:

[0026] A layer of the narrow bandgap perovskite layer having the narrow bandgap perovskite surface modification layer on the hole transport layer II is prepared, annealed and cooled to room temperature; and a layer of the electron transport layer II is arranged on the narrow bandgap perovskite surface modification layer and the narrow bandgap perovskite layer.

[0027] Furthermore, the material structure general formula of the wide bandgap perovskite layer and the narrow bandgap perovskite layer is ABX3, wherein:

[0028] A is selected from CH3NH3 + (MA + )、CH(NH2)2 + (FA + ), Rb + or Cs + Any one or a combination of at least two of the following:

[0029] B is selected from Pb 2+ ,Ge 2+ Sn 2+ Any one or a combination of at least two of the following:

[0030] X is selected from Cl - Br - or I - Any one or a combination of at least two of the following.

[0031] Furthermore, the wide bandgap perovskite layer has a bandgap width of 1.65 to 1.85 eV, and A in the general structural formula is selected from CH3NH3 + (MA + )、CH(NH2)2 + (FA + ), Rb + or Cs + Any one or a combination of at least two of the following, B is Pb 2+ , X is selected from Cl - Br - or I - Any one or a combination of at least two of the following; the thickness of the wide bandgap perovskite layer is 200nm to 1000nm.

[0032] Furthermore, the narrow bandgap perovskite layer has a bandgap width of 1.21 to 1.55 eV, and A in the general structural formula is selected from CH3NH3 + (MA + )、CH(NH2)2 + (FA + ), Rb + or Cs + Any one or a combination of at least two of the following, B is Pb 2+ Sn 2+ Any combination of two, X is I - ; The thickness of the narrow bandgap perovskite layer is 500nm to 1500nm.

[0033] Furthermore, the hole transport layer I and the hole transport layer II include any one or more combinations of organic P-type polymers, P-type metal compounds and self-assembled monolayers.

[0034] The present invention provides a low-dimensional carbon material-based all-perovskite stacked battery intermediate layer structure, which is uniformly dispersed or covered on the ALD dense protective layer by selecting appropriate low-dimensional carbon materials and their combinations, and is located between the ALD dense protective layer and the hole transport layer II, so as to efficiently recombine the photogenerated charges collected from the wide and narrow band gaps. This low-cost material can be prepared and deposited by the full solution method to replace the original evaporation of gold or sputtering ITO, which not only reduces the cost but also effectively reduces parasitic absorption and shortens the deposition time, while avoiding the diffusion of precious metals and significantly improving the stability of the device. This solution is of great significance to the industrialization of all-perovskite stacked calcium battery technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a structural diagram of the intermediate layer structure of a full perovskite stacked battery based on low-dimensional carbon materials described in the present invention;

[0036] Figure 2 The transmission spectrum of the multilayer graphene oxide composite material used in the intermediate layer structure of the all-perovskite tandem battery based on low-dimensional carbon materials described in the present invention on a glass substrate (Example 1) and the transmission spectrum of 2nm gold evaporated on a glass substrate (Comparative Example 1) used in the intermediate layer structure of the traditional all-perovskite tandem battery;

[0037] Figure 3 A JV curve diagram of a device of an intermediate layer structure of a full perovskite stacked battery based on a low-dimensional carbon material according to the present invention, i.e., a battery based on an intermediate layer structure of a graphene composite material (optimal device (Example 2)), a battery based on an intermediate layer structure without a composite material (optimal device (Comparative Example 2)), and a conventional battery based on an intermediate layer structure of 2nm gold (optimal device (Comparative Example 3));

[0038] Figure 4 The EQE spectrum of the all-perovskite tandem battery with an intermediate layer structure based on a graphene composite material (optimal device (Example 2)) of the all-perovskite tandem battery intermediate layer structure based on a low-dimensional carbon material described in the present invention and the EQE spectrum of the tandem battery with a traditional intermediate layer structure based on 2nm gold (optimal device (Comparative Example 3)), including the wide bandgap part and the narrow bandgap part of the tandem battery and the total EQE spectrum;

[0039] Figure 5 The scanning electron microscope images are of the intermediate layer structure of the graphene composite material of the intermediate layer structure of the all-perovskite stacked battery based on low-dimensional carbon material (Example 2) described in the present invention and the scanning electron microscope images of the traditional intermediate layer structure based on 2nm gold (Comparative Example 3). DETAILED DESCRIPTION

[0040] The present invention is further described in detail below based on the accompanying drawings and embodiments. The described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] This scheme provides an intermediate layer structure of all-perovskite tandem battery based on low-dimensional carbon materials, which can also be used in other perovskite tandem battery devices, such as perovskite / crystalline silicon tandem battery, perovskite / organic tandem battery and perovskite / copper indium gallium selenide tandem battery, etc. Figure 1 As shown, an intermediate layer structure of a full perovskite stacked battery based on a low-dimensional carbon material includes a wide bandgap perovskite half-cell at the bottom and a narrow bandgap perovskite half-cell at the top, and an intermediate layer structure is arranged between the wide bandgap perovskite half-cell and the narrow bandgap perovskite half-cell;

[0042] The intermediate layer structure includes an electron transport layer I, an ALD dense protection layer, a low-dimensional carbon material charge recombination layer and a hole transport layer II arranged from bottom to top, and the preparation steps are as follows:

[0043] Step (1) preparing a layer of the electron transport layer I on the top of the wide bandgap perovskite half-cell;

[0044] Step (2) preparing a layer of the ALD dense protective layer on the electron transport layer I by ALD method;

[0045] Step (3) After the ALD dense protective layer is cooled to room temperature, a low-dimensional carbon material precursor liquid is disposed on the ALD dense protective layer by deposition to obtain the low-dimensional carbon material charge recombination layer, and annealing and cooling to room temperature; the annealing temperature is 60° C. to 150° C., the annealing time is 1 minute to 100 minutes, and the annealing environment is in an air environment or in a glove box protected by an inert gas;

[0046] Step (4) preparing a hole transport layer II acting on the narrow bandgap perovskite half-cell on the low-dimensional carbon material charge recombination layer, annealing and cooling to room temperature.

[0047] The wide bandgap perovskite half-cell described in this embodiment includes a hole transport layer I, a wide bandgap perovskite layer and a wide bandgap perovskite surface modification layer arranged from bottom to top;

[0048] The preparation steps of the wide bandgap perovskite half-cell are as follows:

[0049] Disposing a layer of the hole transport layer I on a clean conductive substrate, annealing and cooling to room temperature;

[0050] Preparing a layer of the wide bandgap perovskite layer having the wide bandgap perovskite surface modification layer on the hole transport layer I, annealing and cooling to room temperature;

[0051] The narrow bandgap perovskite half-cell includes a narrow bandgap perovskite layer, a narrow bandgap perovskite surface modification layer and an electron transport layer II arranged from bottom to top;

[0052] The preparation steps of the narrow bandgap perovskite half-cell are as follows:

[0053] Preparing a layer of the narrow bandgap perovskite layer having the narrow bandgap perovskite surface modification layer on the hole transport layer II, annealing and cooling to room temperature;

[0054] A layer of the electron transport layer II is arranged on the narrow-bandgap perovskite surface modification layer and the narrow-bandgap perovskite layer.

[0055] The above steps can be summarized as follows:

[0056] Step S1, preparing a bottom cell, i.e., the wide bandgap perovskite half cell; comprising:

[0057] Step S1.1, a hole transport layer I for wide bandgap battery is prepared on a clean conductive glass substrate by spin coating, spray coating, slit coating, immersion method, chemical vapor deposition (CVD), evaporation, sputtering, ALD and other methods, annealed and cooled to room temperature;

[0058] Step S1.2, preparing a wide bandgap perovskite layer (including a wide bandgap perovskite surface modification layer) on the hole transport layer I by spin coating, spray coating, slit coating, blade coating, multi-source evaporation, dry-wet mixing, etc., annealing and cooling to room temperature;

[0059] Step S2, preparing an intermediate layer structure; comprising:

[0060] Step S2.1, preparing an electron transport layer I on the wide bandgap perovskite layer and the wide bandgap perovskite surface modification layer by spin coating, spray coating, slit coating, immersion method, CVD, evaporation, Sputtering, ALD, etc.;

[0061] Step S2.2, preparing a dense transparent metal oxide protective layer on the electron transport layer I by ALD method, that is, ALD dense protective layer, such as SnO2-x protective layer;

[0062] Step S2.3, after cooling to room temperature, take out, deposit a precursor solution of a low-dimensional carbon material such as an aqueous solution of graphene on the ALD SnO2-x in an air atmosphere by a solution method such as spin coating to obtain a charge recombination layer of a low-dimensional carbon material; prepare a layer of a low-dimensional carbon material composite layer on the ALD dense protective layer by a solution method such as spin coating, spraying, immersion, slit coating, etc., anneal and cool to room temperature;

[0063] Step S2.4, preparing a hole transport layer II for narrow bandgap batteries on the low-dimensional carbon material composite layer by spin coating, spray coating, slit coating, immersion method, CVD, evaporation, Sputtering, ALD and other methods, annealing and cooling to room temperature;

[0064] Step S3, preparing a top cell, i.e., the narrow bandgap perovskite half cell; comprising:

[0065] Step S3.1, preparing a narrow bandgap perovskite layer (including a narrow bandgap perovskite surface modification layer) on the hole transport layer II by spin coating, spray coating, slit coating, blade coating, multi-source evaporation, dry-wet mixing, etc., annealing and cooling to room temperature;

[0066] Step S3.2, preparing an electron transport layer II on the narrow bandgap perovskite and its surface modification layer by spin coating, spray coating, slit coating, immersion method, CVD, evaporation, Sputtering, ALD and the like;

[0067] Step S3.3, preparing an electrode layer of the all-perovskite stacked cell on the interface modification layer by methods such as CVD, evaporation, Sputtering, ALD, etc.;

[0068] Finally, the electrodes are evaporated and packaged to prepare a complete all-perovskite tandem solar cell.

[0069] The low-dimensional carbon material precursor solution used in this embodiment is a high-polarity solvent with a concentration range of 0.01 to 10 mg / mL.

[0070] The low-dimensional carbon material precursor liquid is disposed on the ALD dense protective layer by a deposition method, wherein the deposition method includes a dynamic spin coating method and a solution method, wherein:

[0071] The rotation speed of the dynamic spin coating method is 3000 to 10000 rpm, and the time is 5 to 100 seconds;

[0072] The solution method is any one of spraying, dipping and slit coating.

[0073] The raw material of the low-dimensional carbon material charge recombination layer in this embodiment is a low-dimensional carbon material, including any combination of one or more of zero-dimensional carbon material, one-dimensional carbon material and two-dimensional carbon material.

[0074] Specifically, the zero-dimensional carbon materials include graphene quantum dots, nanodiamonds, fullerenes and their derivatives, and carbon dots, and their three-dimensional dimensions are all 1-100 nm;

[0075] The one-dimensional carbon material is a single-walled carbon nanotube, a multi-walled carbon nanotube, a carbene, a carbon fiber, etc., and its size is a diameter of 5-200nm;

[0076] The two-dimensional carbon material is single-layer graphene, multi-layer graphene, graphene oxide, graphyne, graphene derivatives, transition metal carbon / nitrogen / carbonitride (MXenes), etc., and its thickness is 1-200nm;

[0077] In this embodiment, the electrode is a combination of one or more high-conductivity metals such as gold, silver, copper, platinum, and bismuth, wherein the thickness of the metal electrode is 50-500 nm.

[0078] The material structure general formula of the wide bandgap perovskite layer and the narrow bandgap perovskite layer in this embodiment is ABX3, wherein:

[0079] A is selected from CH3NH3 + (MA + )、CH(NH2)2 + (FA + ), Rb + or Cs + Any one or a combination of at least two of the following:

[0080] B is selected from Pb 2+ ,Ge 2+ Sn 2+ Any one or a combination of at least two of the following:

[0081] X is selected from Cl - Br - or I - Any one or a combination of at least two of the following.

[0082] The wide bandgap perovskite layer has a bandgap of 1.65 to 1.85 eV, and A in the general structural formula is selected from CH3NH3 + (MA + )、CH(NH2)2 + (FA + ), Rb + or Cs + Any one or a combination of at least two of the following, B is Pb 2+ , X is selected from Cl - Br - or I -Any one or a combination of at least two of the following; the thickness of the wide bandgap perovskite layer is 200nm to 1000nm.

[0083] The narrow bandgap perovskite layer has a bandgap width of 1.21 to 1.55 eV, and A in the general structural formula is selected from CH3NH3 + (MA + )、CH(NH2)2 + (FA + ), Rb + or Cs + Any one or a combination of at least two of the following, B is Pb 2+ Sn 2+ Any combination of two, X is I - ; The thickness of the narrow bandgap perovskite layer is 500nm to 1500nm.

[0084] In this embodiment, the hole transport layer I and the hole transport layer II include organic P-type polymers (poly(triaryl amine) (PTAA), poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT: PSS), 2,2',7,7'-Tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD), Poly[N,N'- bis(4-butylphenyl)-N,N'-bis(phenyl)-benzi) (Poly-TPD), poly(3-hexylthiophene) (P3HT) etc.), P-type metal compounds (NiOx, VOx, MoC, WO, Cu2O, CuO, CuI2, CuS, CuSCN, Cu2ZnSnS4, copper phthalocyanine, PbS etc.) and self-assembled monolayers (SAM, Such as MeO-2PACz, MeO-4PACz, [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphate (Me-4PACz), (2-(9H-carbazole-9-yl)ethyl)phosphate (2PACz), [4-(9H-carbazole-9-yl)butyl]phosphate (4PACz), [4-(7H-dibenzocarbazole-7-yl)butyl]phosphate (4PADCB) and a series of phosphate molecules) or any one or more combinations thereof.

[0085] The electron transport layer I and the electron transport layer II include organic N-type polymers (poly(ethylene glycol) (PEG), poly(dimethylsiloxane-block-methylmethacrylate) (PDMS-b-PMMA), polarpolyfluorene (PF-EP), polyfluorene bearing lateral amino groups (PFN), polyfluorene bearing quaternary ammonium groups in the side chains (WPF-oxy-F), fluorene alternating and random copolymer bearing cationic groups in the alkyl side chains (PFNBr DBT15), fluorene alternating and random copolymer bearing cationic groups in the alkyl side chains (PFPNBr), poly (ethylene oxide) (PEO) etc.), N-type inorganic substances (LiF, CsP, SnO 2-x 、TiO 2-x , ZnO, single-walled carbon nanotubes, etc.) and small molecules (fullerene (C 60 ), and its derivatives such as phenyl-C61 -butryric acid methyl ester (PCBM), indeneC 60 bis adduct (ICBA), etc.) or any one or more combinations of the above.

[0086] Comparative Example 1

[0087] In a comparative example, a high-purity gold film prepared by thermal evaporation is provided. The substrate is a glass substrate that has been cleaned and treated with an ultraviolet ozone cleaner for 15 minutes. The thickness of the thin film is 2 nm, and the evaporation rate is 0.01 nm / s. Example 1

[0088] This embodiment provides a thin film graphene film prepared by a solution method, wherein the substrate is a glass substrate that has been cleaned and treated with an ultraviolet ozone cleaning agent for 15 minutes, and the graphene precursor solution has a concentration of 0.5 mg / mL and is dynamically spin-coated on the glass substrate at a speed of 5000 rpm, immediately transferred to a hot stage for annealing at 100° C. for 30 minutes, and then cooled to room temperature.

[0089] Comparative Example 2

[0090] The present comparative example provides a full perovskite stacked solar cell, wherein a cleaned (ultrasonic cleaning in the order of acetone, IPA, acetone, and IPA for 20 minutes, drying at 65°C, and ultraviolet ozone treatment for 15 minutes) conductive glass is transferred to a nitrogen glove box, and then a self-assembled molecular layer (0.75 mg / mL MeO-2PACz in isopropanol) is dynamically spin-coated on the conductive glass substrate at a rotation speed of 5000 rpm, and the substrate is immediately transferred to a hot stage for annealing at 110°C for 10 minutes, and then cooled to room temperature, which is a hole transport layer I.

[0091] Then, 50 uL of wide bandgap perovskite precursor solution (1.2 M Cs 0.4 FA 0.6 PbBr1I2: CsI, FAI, PbBr2 and PbI2 dissolved in DMF:DMSO = 4vol:1vol, 5mol% MAPbCl3 and 0.7mg / mL PEABr were added as additives) and spin-coated on the hole transport layer I at 1000 rpm for 5 seconds and 5000 rpm for 30 seconds. The perovskite film was blown dry with a nitrogen gun 15 seconds before the end of the program. At the end, the perovskite film was just a brown transparent semi-solid film, and was immediately transferred to a hot stage for annealing at 100°C for 20 minutes. After cooling to room temperature, choline chloride solution (1mg / mL in isopropanol) was dynamically spin-coated on the wide bandgap perovskite layer at 6000 rpm for 30 seconds and immediately annealed at 100°C for 5 minutes.

[0092] The film was transferred to a thermal evaporator and heated under high vacuum (<5 × 10 -5 Pa) was used to deposit a 25 nm thick C 60 , which is the electron transport layer I. Then it is transferred to the atomic layer deposition equipment and deposited under low vacuum (<5×10 -2 Pa) deposited ~20nm SnO 2-x , the chamber temperature is 80℃, and the deposition rate is ~0.1nm / cycle. Take it out and transfer it to the air environment to cool to room temperature, then dynamically spin-coat a layer of PEDOT:PSS (commercial 4083 solution) on the above film at a speed of 5000 rpm, which is the hole transport layer II. After cooling to room temperature, transfer it to a nitrogen glove box.

[0093] 80 uL of narrow bandgap perovskite precursor solution (2 M Cs 0.2 FA 0.8 Pb 0.5 Sn 0.5I3: CsI, FAI, SnI2 and PbI2 dissolved in DMF:DMSO = 2vol:1vol, 5mol% SnF2 and 1mg / mL PEACl were added as additives) and spin coated on the hole transport layer II at a speed of 1000 rpm for 10 seconds and 4000 rpm for 30 seconds. 200uL ethyl acetate was poured on the narrow bandgap perovskite liquid film 25 seconds before the end of the program. At the end, the perovskite film was just a dark brown transparent semi-solid film. It was immediately transferred to the hot stage and annealed at 120°C for 10 minutes. After cooling to room temperature, EDAI2 alkaline solution (1mg / mL in isopropanol) was dynamically spin coated on the wide bandgap perovskite layer at 6000 rpm for 30 seconds and immediately annealed at 100°C for 3 minutes. Transfer to a thermal evaporation device and evaporate under high vacuum (<5 × 10 -5 C with thicknesses of 20 nm, 6 nm, and 80 nm were deposited at 100 Pa. 60 , BCP and Cu.

[0094] Comparative Example 3

[0095] This comparative example provides a full perovskite tandem solar cell, which differs from comparative example 2 only in that in ALDSnO 2-x An ultra-thin layer of gold is thermally evaporated on the layer with a thickness of ~2 nm and an evaporation rate of ~0.01 nm / s, and then taken out to an air environment to deposit the hole transport layer II. Example 2

[0096] This embodiment provides a full perovskite tandem solar cell, which is different from Comparative Example 2 only in that in ALDSnO 2-x After the layer deposition was completed, it was taken out and transferred to an air environment to cool to room temperature, and then the graphene solution (0.5 mg / ml dispersed in water) was dynamically spin-coated on the above ALD SnO 2-x The layer was then annealed at 100°C for 30 minutes, cooled to room temperature, and then the hole transport layer II was deposited in an air environment.

[0097] Performance Testing

[0098] The optimal photovoltaic performance parameters of the stacked cells provided in Comparative Example 2, Comparative Example 3 and Example 2, as well as the photovoltaic performance statistics of the 15 stacked cells provided, including open circuit voltage (Voc), short circuit current (Jsc), fill factor (FF) and initial photoelectric conversion efficiency (PCE) are listed in Table 1.

[0099] In addition, taking Example 1 and Comparative Example 1 as examples, the light transmittance of the low-dimensional carbon material charge recombination layer and the traditional gold charge recombination layer was compared. The results are as follows: Figure 2As shown, Comparative Example 1 (traditional gold charge recombination layer) has non-negligible parasitic absorption in the visible light range (300-800 nanometers), while Example 1 (low-dimensional carbon material charge recombination layer) has no parasitic absorption in the entire response range of the stacked battery (300-1100 nanometers), which shows that the theoretical current density and efficiency of the all-perovskite stacked battery based on the low-dimensional carbon material charge recombination layer are higher than those based on gold. Figure 3 As shown, when deposited on a wide bandgap half-cell, the distribution of the gold charge recombination layer (Comparative Example 3) is discontinuous but relatively dense, and the two-dimensional graphene sheet can fit tightly on the wide bandgap perovskite layer, and the number of layers is only a few molecular layers of graphene (Example 2). Although the coverage is not high, the charge recombination catalytic efficiency can still be fully guaranteed.

[0100] Based on the efficiency of the all-perovskite tandem cells with different charge composite materials in the middle layer, the photovoltaic performance results of the cells in Example 2 and the champion cells in Comparative Examples 2 and 3 are shown in Tables 1 and Figure 4 shown.

[0101] When there is no charge recombination layer (Comparative Example 2), although the current is relatively high (no parasitic absorption), the filling factor is very low. This is because the photogenerated charges from the wide and narrow band gaps cannot be effectively recombined; when the charge recombination layer is gold (Comparative Example 3), although it can be effectively recombined (high filling factor), the current is relatively low due to parasitic absorption; when the charge recombination layer is graphene (Example 2), it can be effectively recombined (high filling factor) and there is no parasitic absorption (relatively high current), thereby increasing the efficiency from 24.90% to 25.62%.

[0102] Table 1

[0103] Voc (V) <![CDATA[Jsc (mA cm -2 )]]> FF PCE (%) Comparative Example 2 - Optimal 1.980 15.42 0.6164 18.82 Comparative Example 3 - Optimal 2.030 15.30 0.8017 24.90 Example 2 - Best 2.040 15.86 0.7919 25.62 Comparative Example 3 - Statistics 2.024± 0.0091 15.23± 0.064 0.7862± 0.0073 24.24± 0.315 Example 2 - Statistics 2.027 ± 0.0082 15.64 ±0.078 0.7894 ±0.0053 25.02 ±0.266

[0104] Depend on Figure 5 It can be seen that the all-perovskite tandem cell provided by the present invention has no significant effect on the EQE of the wide bandgap part of the tandem cell device by using the above-mentioned low-dimensional carbon material composite layer that can efficiently recombine photogenerated charges with or without parasitic absorption, and the EQE of the narrow bandgap part is significantly improved in the 600-800 nm region, resulting in a final integrated current density increase of 0.7 mA cm -2 , which is completely consistent with the JV test results of the battery, which proves that the parasitic absorption-free characteristics of the composite layer based on low-dimensional carbon materials can indeed directly lead to an increase in the overall current density of the battery.

[0105] The above description is only for illustrating the implementation mode of the present invention and is not intended to limit the present invention. For those skilled in the art, any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An intermediate layer structure of a full perovskite stacked battery based on low-dimensional carbon materials, characterized in that: It includes a wide bandgap perovskite half-cell at the bottom and a narrow bandgap perovskite half-cell at the top, and an intermediate layer structure is arranged between the wide bandgap perovskite half-cell and the narrow bandgap perovskite half-cell; The intermediate layer structure includes an electron transport layer I, an ALD dense protection layer, a low-dimensional carbon material charge recombination layer and a hole transport layer II arranged from bottom to top, and the preparation steps are as follows: Step (1) preparing a layer of the electron transport layer I on the top of the wide bandgap perovskite half-cell; Step (2) preparing a layer of the ALD dense protective layer on the electron transport layer I by ALD method; Step (3) After the ALD dense protective layer is cooled to room temperature, a low-dimensional carbon material precursor solution is disposed on the ALD dense protective layer by deposition to obtain the low-dimensional carbon material charge recombination layer, and annealing and cooling to room temperature; the annealing temperature is 60° C. to 150° C., and the annealing time is 1 minute to 100 minutes; Step (4) preparing a hole transport layer II acting on the narrow bandgap perovskite half-cell on the low-dimensional carbon material charge recombination layer, annealing and cooling to room temperature; The raw material of the low-dimensional carbon material charge recombination layer is a low-dimensional carbon material, including any combination of one or more of a zero-dimensional carbon material and a two-dimensional carbon material, and the low-dimensional carbon material charge recombination layer does not completely cover the ALD dense protective layer; The zero-dimensional carbon material is graphene quantum dots; The two-dimensional carbon material is multilayer graphene.

2. According to claim 1, a low-dimensional carbon material-based all-perovskite stacked battery intermediate layer structure is characterized in that: The low-dimensional carbon material precursor solution is a high-polarity solvent with a concentration range of 0.01 to 10 mg / mL.

3. The intermediate layer structure of the all-perovskite stacked battery based on low-dimensional carbon materials according to claim 2 is characterized in that: In step (3), the low-dimensional carbon material precursor liquid is disposed on the ALD dense protective layer by a deposition method, wherein the deposition method includes a dynamic spin coating method and a solution method, wherein: The rotation speed of the dynamic spin coating method is 3000 to 10000 rpm, and the time is 5 to 100 seconds; The solution method is any one of spraying, dipping and slit coating.

4. The intermediate layer structure of the all-perovskite stacked battery based on low-dimensional carbon materials according to claim 1 is characterized in that: The wide bandgap perovskite half-cell comprises a hole transport layer I, a wide bandgap perovskite layer and a wide bandgap perovskite surface modification layer arranged from bottom to top; The narrow-bandgap perovskite half-cell comprises a narrow-bandgap perovskite layer, a narrow-bandgap perovskite surface modification layer and an electron transport layer II arranged from bottom to top.

5. The intermediate layer structure of the all-perovskite stacked battery based on low-dimensional carbon material according to claim 4, characterized in that: The preparation steps of the wide bandgap perovskite half-cell are as follows: Disposing a layer of the hole transport layer I on a clean conductive substrate, annealing and cooling to room temperature; Preparing a layer of the wide bandgap perovskite layer having the wide bandgap perovskite surface modification layer on the hole transport layer I, annealing and cooling to room temperature; The preparation steps of the narrow bandgap perovskite half-cell are as follows: Preparing a layer of the narrow bandgap perovskite layer having the narrow bandgap perovskite surface modification layer on the hole transport layer II, annealing and cooling to room temperature; A layer of the electron transport layer II is arranged on the narrow-bandgap perovskite surface modification layer and the narrow-bandgap perovskite layer.

6. The intermediate layer structure of the all-perovskite stacked battery based on low-dimensional carbon material according to claim 4 or 5, characterized in that: The material structure general formula of the wide bandgap perovskite layer and the narrow bandgap perovskite layer is ABX3, wherein: A is selected from CH3NH3 + (MA + )、CH(NH2)2 + (FA + ), Rb + or Cs + Any one or a combination of at least two of the following: B is selected from Pb 2+ ,Ge 2+ Sn 2+ Any one or a combination of at least two of the following: X is selected from Cl - Br - or I - Any one or a combination of at least two of the following.

7. The intermediate layer structure of the all-perovskite stacked battery based on low-dimensional carbon materials according to claim 6, characterized in that: The wide bandgap perovskite layer has a bandgap width of 1.65 to 1.85 eV, and A in the general structural formula is selected from CH3NH3 + (MA + )、CH(NH2)2 + (FA + ), Rb + or Cs + Any one or a combination of at least two of the following, B is Pb 2+ , X is selected from Cl - Br - or I - Any one or a combination of at least two of the following: The thickness of the wide bandgap perovskite layer is 200nm-1000nm.

8. The intermediate layer structure of the all-perovskite stacked battery based on low-dimensional carbon materials according to claim 6, characterized in that: The narrow bandgap perovskite layer has a bandgap width of 1.21 to 1.55 eV, and A in the general structural formula is selected from CH3NH3 + (MA + )、CH(NH2)2 + (FA + ), Rb + or Cs + Any one or a combination of at least two of the following, B is Pb 2+ Sn 2+ Any combination of two, X is I - ; The thickness of the narrow bandgap perovskite layer is 500nm-1500nm.

9. The intermediate layer structure of the all-perovskite stacked battery based on low-dimensional carbon materials according to claim 4, characterized in that: The hole transport layer I and the hole transport layer II include any one or more combinations of organic P-type polymers, P-type metal compounds and self-assembled monolayers.

Citation Information

Patent Citations

  • Perovskite tandem solar cells based on a tunneling layer of two-dimensional layered metal carbides and metal nitrides

    US20240292637A1